Supervisory adaptive nonlinear control for seismic alleviation of inelastic asymmetric buildings equipped with MR dampers. (1st December 2018) - Zafarani, Mohammad M.; Halabian, Amir M.
Highlights: An adaptive model-based control strategy for plan asymmetric buildings is developed. The adaptive nonlinear stiffness matrix is introduced in a semi active Clipped Optimal algorithm. The applicability of the method is examined on a mass asymmetric building equipped with MR dampers. The results highlighted the successfulness of the proposed strategy in improving the structure's torsional behavior. Abstract: Many structures under extreme dynamic loadings experience nonlinear behavior causing changes in structural characteristics such as stiffness and damping. In these cases, the analytical modeling can no longer be introduced by an algebraic function to control model-based algorithms and therefore, adaptive strategies with adjustable parameters can be a proper method to deal with time-varying properties of structural systems. The current research aimed to develop an adaptive model-based control strategy to control nonlinear torsional behavior of plan asymmetric buildings. This approach is based on introducing the adaptive nonlinear stiffness matrix into an active model-based control strategy such as LQR or LQG and semi active Clipped Optimal algorithm. To examine the applicability of the proposed adaptive method in mitigating the inelastic torsional effects of asymmetric buildings, a set of parametric studies were conducted using a mathematical model of an inelastic one-storey plan-asymmetric building equipped with Magneto-Rheological (MR) dampers. To simulate the non-linear behavior of the controlled asymmetric structure, Fiber Element modelling was employed to simulate nonlinear behaviour of both beam and column members. The performance of the proposed method was compared with some other control methods such as fuzzy logic controllers. The results showed that this method was successful in improving the torsional nonlinear behavior of the asymmetric building used in this study subjected to ordinary and strong ground motions.